Конфлікт інтересів у антикорупційному законодавстві України: засіб запобігання корупції чи правовий абсурд? - Аніщенко, Михайло Анатолійович; Алексєєв, Олександр Германович; Гамбург, Леонід Самойлович; Дічко, Ганна Олегівна; Anishchenko, M. A.; Alekseev, A.; Hamburg, L.; Dichko, H. (Київ: Всеукр. громад. орг. "Майбутнє країни", Ужгород. нац. ун-т., 2018)
The article discusses the problematic issues related to the institution of conflict of interest, which in the new anti-corruption legislation of Ukraine acquired innovative content after the official interpretation of this legal category by the National Agency for the Prevention of Corruption of Ukraine (NACP). The legislation does not define any typical situations that are not subject to the norms regulating the conflict of interests, therefore a number of constitutional rights and freedoms of a person and citizen are outside the prescriptions of the Law of Ukraine ―On the Prevention of Corruption‖, which forms a contradiction between them. The unequal application of the norms of anticorruption legislation to similar legal relations with the NACP is stated. Potential and real conflicts of interests are a permanent reality in the activities of state institutions, enterprises, organizations, therefore the legal regulation of a conflict of interests needs to be seriously improved.
Conflict of interests in the anti-corruption legislation of Ukraine: a means of preventing corruption or legal absurdity?
Keywords: антикорупційне законодавство; запобігання коруації; конфлікт івнтересів; приватний інтерес; друдні стосунки; близькі особи; відносини підпорядкування; anti-corruption legislation; prevention of corruption; conflict of interests; private interest; friendly relations; close people; subordination relations